(untitled) (Analysis of International Sciences, 2024)
This article discusses the problems of today’s implementation of the main goals of budget revenues, such as fulfilling state tasks, ensuring economic stability and improving the well-being of the population. In addition, this article focuses on the same aspects, that is, the stability of the budget is one of the most important indicators characterizing the state of the country’s economy and, above all, its social sphere. It was discussed that new reforms are being implemented in our country in order to ensure the perfect ratio and completeness of the sources of their formation.